RNA-Seq Revealed Expression of Many Novel Genes Associated With Leishmania donovani Persistence and Clearance in the Host Macrophage - Shadab, Mohammad; Das, Sonali; Banerjee, Anindyajit; Sinha, Roma; Asad, Mohammad; Kamran, Mohd; Maji, Mithun; Jha, Baijayanti; Deepthi, Makaraju; Kumar, Manoharan; Tripathi, Abhishek; Kumar, Bipin; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Host as well as parasite specific factors, are equally crucial, in allowing either the Leishmania parasites to dominate, or host macrophages to resist infection. To identify such factors, we infected murine peritoneal macrophages with either the virulent (vAG83) or the non-virulent (nvAG83) parasites of L. donovani. Then, through dual RNA-seq, we simultaneously elucidated the transcriptomic changes occurring both in the host and the parasites. Through Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, of the differentially expressed (DE) genes, we showed that the vAG83 infected macrophages exhibit biased anti-inflammatory responses compared to the macrophages infected with the nvAG83. Moreover, the vAG83 infected macrophages displayed suppression of many important cellular processes including protein synthesis. Further, through protein-protein interaction study, we showed a significant downregulation in the expression of many hubs and hub-bottleneck genes in macrophages infected with the vAG83 as compared to the nvAG83. Cell signaling study showed that these two parasites activated MAPK and PI3K-AKT signaling pathways, differentially, in the host cells. Through gene ontology analyses of the parasite specific genes, we discovered that the genes for virulent factors and parasite survival were significantly upregulated in the intracellular amastigotes of the vAG83. In contrast, genes involved in the immune stimulations, and those involved in negative regulation of cell cycle and transcriptional regulation, were upregulated in the nvAG83. Collectively, these results depicted a differential regulation in the host and the parasite specific molecules, during persistence and clearance of the parasites, in vitro.